Genetics of Infantile Bilateral Striatal Necrosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The gene mutation causing autosomal recessive infantile bilateral striatal necrosis (IBSN) was identified in eight consanguineous Israeli Bedouin families, in a study at Schneider Children's Medical Center, Petah Tikva, Israel, and other centers.